E-GOVERNMENT DAN PELAYANAN PUBLIK (STUDI TENTANG ELEMEN SUKSES PENGEMBANGAN E-GOVERNMENT DI PEMERINTAH KABUPATEN SLEMAN) - Joko Tri Nugraha (Jurnal Komunikasi dan Kajian Media, 2018)
Since the enactment of Presidential Instruction No. 3 of 2003 on policies and strategies for e-government development, the government is required to be able to utilize the progress of information and communication technology through the development of public services based on e-government. At the national level, many local governments have initiatives to implement e-government. However, conditions in the field found differences between regions for various reasons, such as the limited budgetary factors, infrastructure and human resources. The developed e-government simply indicates that policy compliance is not accompanied by quality improvement. This research was conducted with the aim to map the key elements of successful e-government development in Sleman District as well as identify problems in the implementation of e-government so that the right solution can be formulated. This research use descriptive qualitative method with informant from 28 web manager of OPD in Sleman regency, data analysis technique utilize flow model analysis technique. Keywords: e-government, public service, Sleman Regency